2016
DOI: 10.14715/cmb/2016.62.13.4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mebudipine on myocardial arrhythmia induced by ischemia-reperfusion injury in isolated rat heart

Abstract: Reperfusion of the heart after an ischemic insult may lead to potentially lethal arrhythmias and cardimyocyte cell death via apoptosis and necrosis. In addition, previous studies showed that calcium channel blockers may have a protective role in the myocardium against arrhythmia and irreversible tissue injury. Therefore, this study was aimed to investigate the effects of mebudipine on myocardial arrhythmias and tissue injury induced by ischemia/reperfusion injury in isolated rat hearts. Male Wistar rats (250‑3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…However, limited studies have reported the protective role of T1AM in vivo. Myocardial ischemia reperfusion can lead to lethal ventricular arrhythmias (18). The current data showed that T1AM decreased the incidence of VF, suggesting that T1AM can attenuate MIRI.…”
Section: Discussionsupporting
confidence: 48%
“…However, limited studies have reported the protective role of T1AM in vivo. Myocardial ischemia reperfusion can lead to lethal ventricular arrhythmias (18). The current data showed that T1AM decreased the incidence of VF, suggesting that T1AM can attenuate MIRI.…”
Section: Discussionsupporting
confidence: 48%
“…Myocardial ischemia-reperfusion (I/R) injury is the lesion in which the blood perfusion is restored after the myocardial blood supply is interrupted for a certain period, leading to the injury or dysfunction in ischemic area 1 . Myocardial I/R injury can lead to the impairment of cardiac function and damage of myocardial cells, which increases the risk of cardiovascular events, such as myocardial infarction and arrhythmia, and seriously affects the prognosis of underlying diseases 2 , 3 . In addition, the myocardial I/R injury can limit the application of coronary thrombolysis treatment, interventional therapy and bypass surgery 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The study closely monitored electrocardiographs, assessed serum lactate dehydrogenase (LDH) and creatine phosphokinase (CPK) activities in coronary effluent, and examined the microscopic architecture of the myocardium. Mebudipine demonstrated a reduction in ventricular arrhythmias, an improvement in edema and inflammation, and decreased tissue damage compared to the control group (15).…”
Section: Effects On Heart Myocardial Arrhythmia Induced By Ischemia-r...mentioning
confidence: 81%
“…Following an ischemic injury, reestablishing blood flow to the heart can lead to hazardous cardiac arrhythmias and the death of myocardial cells through apoptosis and necrosis. Calcium channel blockers (CCBs) have been recognized for their ability to safeguard the myocardium from damage and arrhythmias (15). Ghiasi et al conducted a study to investigate mebudipine's impact on myocardial arrhythmias and tissue injury in isolated rat hearts subjected to ischemia/reperfusion.…”
Section: Effects On Heart Myocardial Arrhythmia Induced By Ischemia-r...mentioning
confidence: 99%